Rule-based spreadsheet data transformation from arbitrary to relational tables - Shigarov, Alexey O.; Mikhailov, Andrey A. (Information systems (Oxford), 2017)
•Spreadsheet data transformation can be considered as table understanding.•The two-layered table object model represents arbitrary spreadsheet tables.•Our rule-based language enables to express consecutive steps of table understanding.•Execution of the rules provides recovering implicit table semantic (structure).•A rule-set allows converting arbitrary tables of the same genre into databases. The paper discusses issues of rule-based data transformation from arbitrary spreadsheet tables to a canonical (relational) form. We present a novel table object model and rule-based language for table analysis and interpretation. The model is intended to represent a physical (cellular) and logical (semantic) structure of an arbitrary table in the transformation process. The language allows drawing up this process as consecutive steps of table understanding, i. e. recovering implicit semantics. Both are implemented in our tool for spreadsheet data canonicalization. The presented case study demonstrates the use of the tool for developing a task-specific rule-set to convert data from arbitrary tables of the same genre (government statistical websites) to flat file databases. The performance evaluation confirms the applicability of the implemented rule-set in accomplishing the stated objectives of the application.